Lectotypification of names in the genus Lycianthes (Solanaceae) - Dean, Ellen A.; Reyes, Miriam (Phytotaxa, 2018)
As part of a revision of the Mexican and Central American species of the genus Lycianthes (Solanaceae), 15 names or synonyms in the genus, including many names published by the German botanist Georg Bitter, are lectotypified.